Exploitation of Heterosis for Seed Yield and its Contributing Traits in CMS Based Hybrids of Indian Mustard [Brassica juncea (L.) Czern and Coss] - Patel, D. A.; Patel, D. K.; Patel, J. R.; Prajapati, K. P.; Patel, P. J.; Patel, A. B. (International Journal of Bio-resource and Stress Management, 2021)
In the present study, line× tester analysis was carried out at Castor-Mustard Research Station, S. D. Agricultural University, Sardarkrushinagar, Gujarat, India during rabi 2018–19 (October 2018 to February 2019) in order to estimate all three types of heterosis (relative heterosis, heterobeltiosis and economic heterosis) for identification of superior cross combinations of Indian mustard [Brassica juncea (L.) Czern&Coss]. Thirty-five hybrids along with five CMS lines, seven testers and check GDM 4 were evaluated for ten different traits. The F1 generation of all the crosses exhibited fertility restoration with pollen fertility except F1 crosses with Vardan, Rohini and SKM 319 fertile line (0%). The remaining crosses exhibited pollen fertility ranging from 68.26% (Kranti×SKM 303) to 85.17% (Kranti×Mori ‘R’ 1-18). The analysis of variance for parents, hybrids and parents vs. hybrids revealed that mean sum of squares of parents were highly significant for majority of the characters except days to maturity. Whereas, hybrids differed highly significant for all the characters. Comparison of mean squares due to parents vs. hybrids was found significant for almost all the characters except number of seeds siliqua-1 and oil content. This indicates that considerable amount of genetic variability present among the parents and hybrids for all the characters studied. On the basis of per se performance, three hybrids viz., Kranti×Mori ‘R’ 1-18, SKM 9928×PusaAgrani and SKM 9928×Mori ‘R’ 1-18 were foundpromising for seed yield plant-1 over the standard check GDM 4.With respect to heterosis, one of the hybrid Kranti×Mori ‘R’ 1-18 (17.85 %)manifested significant and positive standard heterosis for seed yield plant-1.